ANALISIS BIBLIOMETRIKA PRODUKTIVITAS PENGARANG ARTIKEL JURNAL BERKALA ARKEOLOGI DENGAN MENGGUNAKAN DALIL HUKUM LOTKA - Bayu Indra Saputro (Berkala Arkeologi, 2011)
This paper aim to present the result of research to analyse the level of author productivity in Berkala Arkeologi journal. The approach that I use is Lotka Law. The law says that if among a hundred people can produce one article, then there will be a quarter of them who produce two articles, there will be one ninth of them will produce three articles, and there will be one sixteenth of them produce 4 articles and so on. This is called the inverse square law of Lotka about author productivity. This paper also describes the statistical methods used to test the correlation between the author and the amount of articles produced, K-S test, a statistical test that is classified into Nonparametric Statistics, used to test the degree of closeness of two sets of data or two distribution (Goodness of fit). From the result this study the author of the Berkala Arkeologi journal in this years 1980-2009 is 138 people. Articles written as many as 392 articles. Based on calculations by the law of Lotka it is found that the productivity of authors for each article is a result of 44 816%, the author of two articles which generate as much as 18,003%, the author of many articles as 10.560% produces 3 and so on.